Pengembangan Usaha Berbasis Digital Pada Masa Pandemi Covid-19 - Nurjannah (Journal of Economic Education and Entrepreneurship Studies, 2022)
This study aims to determine the development of digital-based businesses during the Covid-19 pandemic. This study used a qualitative approach and descriptive method. The data collection used was an interview technique. Informants were determined by purposive sampling technique with certain criteria, so that there were 2 respondents in this study who were sellers of digital-based processed ice lolly. The data analysis phase carried out in this study consisted of data reduction, then data presentation. And the next data analysis is to draw conclusions on the information that has been obtained.